Food Traditions and Landscape Histories of the Indian Ocean World: Theoretical and Methodological Reflections. (1st February 2015) - Rangan, Haripriya; Alpers, Edward A.; Denham, Tim; Kull, Christian A.; Carney, Judith
Abstract : Environmental histories of plant exchanges have largely centred on their economic importance in international trade and on their ecological and social impacts in the places where they were introduced. Yet few studies have attempted to examine how plants brought from elsewhere become incorporated over time into the regional cultures of material life and agricultural landscapes. This essay considers the theoretical and methodological problems in investigating the environmental history, diversity and distribution of food plants transferred across the Indian Ocean over several millennia. It brings together concepts of creolisation, syncretism, and hybridity to outline a framework for understanding how biotic exchanges and diffusions have been translated into regional landscape histories through food traditions, ritual practices and articulation of cultural identity. We use the banana plant - which underwent early domestication across New Guinea, South-east Asia and peninsular India and reached East Africa roughly two thousand years ago - as an example for illustrating the diverse patterns of incorporation into the cultural symbolism, material life and regional landscapes of the Indian Ocean World. We show that this cultural evolutionary approach allows new historical insights to emerge and enriches ongoing debates regarding the antiquity of the plant's diffusion from South-east Asia to Africa.